Analisis Penerapan Audit Internal Pada Koperasi Unit Desa (KUD) Dwi Tunggal Tania Makmur - Fatmawati, Siti; Arafat, Yasir; Salmah, Ninin Non Ayu (Universitas PGRI Palembang, 2024)
ABSTRACT This study aims to determine the application of internal audit to cooperative compliance according to the Ministry of Cooperatives and UMKM Regulation Number 5 of 2016. The population of this study is a report on findings and the sample of this research is audit results in 2019-2021. The data collection technique for this research was a qualitative descriptive technique which was carried out by means of documentation and interviews. The data used are primary data and secondary data. The results of the study show that the cooperative has not fully complied with the regulations that have been set by conducting an internal audit to find out the weaknesses or deficiencies that exist in the cooperative and can comply with the regulations that have been set. The principle of cooperatives, cooperatives have been managed democratically, membership is voluntary and open, the distribution of the remaining business results is carried out fairly, and the development of cooperatives. Business, cooperatives have not been optimal in carrying out business performance, business planning and control, and financial control, KUD Dwi Tunggal has not complied with controls in its business. Transactions have not been carried out optimally by utilizing services, applying a standard accounting system, and KUD Dwi Tunggal has not fully complied with SAK-ETAP which can be seen from the accumulation of depreciation has not been carried out. Keywords: Internal Audit,Compliance, Cooperatives. ABSTRAK Penelitian ini bertujuan untuk mengetahui penerapan audit internal pada kepatuhan koperasi sesuai Peraturan Kementrian Koperasi dan UMKM Nomor 5 Tahun 2016. Populasi penelitian ini adalah laporan hasil temuan dan sampel penelitian ini adalah hasil audit pada tahun 2019-2021. Teknik pengambilan data penelitian ini adalah teknik deskriptif kualitatif yang dilakukan dengan dokumntasi dan wawancara. Data yang digunakan yaitu data primer dan data sekunder. Hasil penelitian menunjukkan bahwa koperasi belum sepenuhnya mematuhi peraturan yang telah ditetapkan dengan dilakukannya audit internal dapat mengetahui kelemahan atau kekurangan yang ada pada koperasi dan dapat mematuhi peraturan yang telah ditetapkan. Prinsip koperasi, koperasi telah melakukan pengelolaan dilakukan secara demokratis, kenggotaan sukarela dan terbuka, pembagian sisa hasil usaha dilakukan secara adil, dan pengembangan koperasi. Usaha, koperasi belum optimal dalam menjalankan kinerja usaha, perencanaan dan pengendalian usaha, dan pengendalian keuangan, KUD Dwi Tunggal belum mematuhi pengendalian dalam usahanya. Transaksi belum dilakukan secara optimal pemanfaatan pelayanan, penerapan sistem standar akuntansi, dan KUD Dwi Tunggal belum sepenuhnya mematuhi SAK-ETAP yang dapat dilihat dari belum dilakukannya akumulasi penyusutan. Kata kunci: Audit Internal, Kepatuhan, Koperasi.